Analysis of long non‐coding RNA involved in atrazine‐induced testicular degeneration of Xenopus laevis. Issue 4 (24th January 2019) - Sai, Linlin; Qu, Binpeng; Zhang, Juan; Liu, Jian; Jia, Qiang; Bo, Cunxiang; Zhang, Yu; Yu, Gongchang; Han, Ru; Peng, Cheng
Abstract: Long non‐coding RNA (lncRNA) plays a critical role in male germline development. Atrazine (AZ) as an environmental endocrine disrupting chemical (EDCs) can induce male reproductive toxicity in amphibians. Our previous studies demonstrated that AZ can alter gene and circular RNA (circRNA) expression of damaged testes in Xenopus laevis ( X. laevis ). We furthered to investigate the lncRNA expression profiling in the testis of X. laevis . Over 3559 lncRNAs were detected by lncRNA sequencing. AZ induced 40 upregulated and 46 downregulated differentially expressed lncRNAs. KEGG analysis showed that AZ‐affected lncRNAs mainly involve in 19 pathways among which 12 pathways are found in circRNA analysis. This study for the first time demonstrated that AZ can alter lncRNAs which may play a role in testicular degeneration through regulating expressions of functional genes in X. laevis . Our data may provide more insights on the mechanism about male reproductive toxicity of EDCs.